Etnomatematika: Eksplorasi matematika pada tata ruang tui gubuk dan arsitektur rumah adat Segenter - Fauzi, Lalu Muhammad; Gazali, Muhammad; Fauzi, Asri (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
Mathematics is found in many activities of traditional culture. However, many perceive that mathematics is culture-free. Based on the occurring phenomenon, ethnomathematics study is made as the connector between mathematics and culture. The presence of ethnomathematics provides many opportunities to discover unique mathematical ideas exist in the traditional culture. This research aims to explore mathematical ideas in the layout of tui gubuk and the architecture of Segenter traditional house that can be made as mathematics learning sources. This study was a qualitative research with ethnographic method. This study was conducted in the traditional village of Segenter, Sukadana Village, Bayan District. Data were collected through an observation and interviews with Adat figures, cultural anthropologists, and traditional leaders who have the knowledge of the customs and culture of Bayan people, which consisted of three informants. Research results indicate that there are mathematical ideas in the layout of tui gubuk and the architecture of Segenter traditional house that can be made as the learning sources of mathematics and can be developed in mathematics learning, especially in materials of set and geometry, both geometry of space and flat geometry.